2020
DOI: 10.7759/cureus.10114
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sex in the Risk of Mortality From COVID-19 Amongst Adult Patients: A Systematic Review

Abstract: A worldwide outbreak of coronavirus disease 2019 (COVID-19), identified as being caused by the severe acute respiratory syndrome coronavirus 2 (SARS-COV-2), was classified as a Public Health Emergency of International Concern by the World Health Organisation (WHO) on January 30, 2020. Initial sex-disaggregated mortality data emerging from the Wuhan province of China identified male sex as a risk factor for increased COVID-19 mortality. In this systematic review, we aimed to assess the role of sex in the risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 52 publications
5
31
1
3
Order By: Relevance
“…Regarding the gender in our study, males had higher risk of developing severe COVID-19 than females, which is consistent with some reports [ 4 , 24 ]. The differences between different gender may be related to underlying biological differences, diversity of immune responses, sex hormones and a combination of behavioral or lifestyle risk factors [ 25 27 ]. Furthermore, several comorbidities, which disproportionally occur in men, likely contribute to worse COVID-19 outcomes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the gender in our study, males had higher risk of developing severe COVID-19 than females, which is consistent with some reports [ 4 , 24 ]. The differences between different gender may be related to underlying biological differences, diversity of immune responses, sex hormones and a combination of behavioral or lifestyle risk factors [ 25 27 ]. Furthermore, several comorbidities, which disproportionally occur in men, likely contribute to worse COVID-19 outcomes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include the role of comorbidities, as well as decreased efficiency of the immune system related to normal ageing [ 108 ]. Male sex as a risk factor for severe disease is thought to result from a combination of the effect of health behaviours, sex hormone-mediated immune responses, and differential expression of ACE2 between sexes [ 109 ]. Obesity is a risk factor for development of comorbidities such as hypertension, cardiovascular disease, and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Among our study population, 44% were men, which is lower than observed in a recent meta-analysis of 57 studies that found the prevalence of COVID-19 to be 55% among men [ 17 ]. As shown in a systematic review of sixteen studies, including studies from China, United States, Italy, UK and Spain, men had increased disease severity including hospitalisation and ICU admission compared to women [ 18 ]. Although it is not fully understood why men are more susceptible to a severe disease trajectory many factors have been proposed that may underlie these differences including immunological differences, elevated expression of certain factors including angiotensin-converting enzyme 2, differences in hormones (e.g., oestrogen) and also social and behavioural differences [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%